Analisis Evaluasi Kinerja Di PT Energi Unggul Persada - Yosua Simbolon; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Multidisiplin Indonesia, 2023)
Rapid and competitive industrial development encourages companies to improve their performance. Employee performance is an important factor in achieving competitive advantage. Performance evaluation is an integral part of human resource management that measures, manages and improves employee performance. This research was conducted at PT. Energi Unggul Persada (PT. EUP), a palm oil processing company. Pre-research with 20 PT employees. EUPs indicated that most did not regularly participate in performance evaluations, and their understanding of performance evaluations was limited. The research aims to deepen performance evaluation at PT. EUP, identifies factors that influence the performance evaluation process, and explores the benefits for employees and companies. Qualitative research methods involve interviews, observation, and document analysis. The research results are expected to provide valuable insight for PT. EUP in designing more effective strategies to improve employee performance. In a changing business environment, a better understanding of performance evaluation will help companies maximize their human capital and strengthen their position in the competitive market. This research is expected to be a valuable source of information in the company's efforts to achieve a higher level of competitive advantage.